2022
DOI: 10.1038/s41598-022-18814-4
|View full text |Cite|
|
Sign up to set email alerts
|

Gender specific somatic symptom burden and mortality risk in the general population

Abstract: Gender specific all-cause mortality risk associated with a high somatic symptom burden (SSB) in a population-based cohort was investigated. The study population included 5679 women and 5861 men aged 25–74 years from the population-based MONICA/KORA Cohort. SSB was assessed following the Somatic Symptom Scale-8 and categorized as very high (≥ 95th percentile), high (60–95th percentile), moderate (30–60th percentile), and low (≤ 30th percentile). The impact of SSB on all-cause mortality risk within a mean follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…Our findings indicate that being female and older independently increases the likelihood of reporting so-matic symptoms. This observation aligns with previous research on the association between female gender as well as older age on a heightened prevalence of somatic symptomatology [14,15]. In a representative sample of the German population, the authors identified a mean age of 56.1 years and 67.6% of the sample to be female, indicating that both characteristics are more pronounced than in the general population [36].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings indicate that being female and older independently increases the likelihood of reporting so-matic symptoms. This observation aligns with previous research on the association between female gender as well as older age on a heightened prevalence of somatic symptomatology [14,15]. In a representative sample of the German population, the authors identified a mean age of 56.1 years and 67.6% of the sample to be female, indicating that both characteristics are more pronounced than in the general population [36].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, exploring the association between psychobehavioral criteria and levels of symptom reporting is of key importance. This association has garnered substantial attention from scholars and practitioners alike, as it holds potential implications for understanding the interaction of underlying psychological factors with the perception and reporting of somatic symptoms [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%